69.1: Image Quality Assessment of Ultra‐High Resolution Mobile Display Utilizing New RGBW Method. Issue 1 (1st July 2013) - Nakahara, Tae; Sakaigawa, Akira; Okita, Mitsutaka; Ikeda, Kojiro; Mitsui, Masashi; Kabe, Masaaki; Nagatsuma, Toshiyuki; Higashi, Amane
Abstract: In this paper, newly‐developed 5.0‐inch full‐HD (1080 × RGBW × 1920) and 7.0‐inch WQXGA (2560 × RGBW × 1600) prototype LCDs utilizing a new RGBW method are described in detail. The assessment of the image quality of the new RGBW technology is described, such as color image reproducibility, white color tracking in the low power mode and tone curve correction in the outdoor bright mode.